Exploration of newer substrate for fibrinolytic enzyme production by solid state fermentation using Penicillium chrysogenum SGAD12 - SM, Gopinath; TB, Suneetha; GM, Ashwini patil (Journal of Research in Biology, 2011)
Rice chaff - a polished substance extracted from Oryza sativa L. cv. Devamallige was used as a novel substrate for the production of the fibrinolytic enzyme. This vital enzyme is used in thrombolytic therapy, as a clot buster. The production was done by solid state fermentation of rice chaff by Penicillium chrysogenum SGAD12, locally isolated from vegetable markets. Of the 28 strains isolated and screened, Penicillium chrysogenum SGAD12 was found to give an inhibition zone greater than 2 mm. Hence it was identified as the potential organism showing maximum fibrinolytic activity under specified culture conditions. Activity optimization was done under the parameters: Time, Inoculum ratio, Moisture, particle size. The fibrinolytic activity was favourably maximized at 104 hrs, 7% (v/v) inoculum ratio, 35-45 % (v/w) moisture content and 500μm particle size